Transcriptomic Analysis of Salivary Glands of Ornithodoros brasiliensis Aragão, 1923, the Agent of a Neotropical Tick-Toxicosis Syndrome in Humans - Reck, Jose; Webster, Anelise; Dall’Agnol, Bruno; Pienaar, Ronel; de Castro, Minique H.; Featherston, Jonathan; Mans, Ben J. (Frontiers in Physiology, 2021)
Tick salivary glands produce and secrete a variety of compounds that modulate host responses and ensure a successful blood meal. Despite great progress made in the identification of ticks salivary compounds in recent years, there is still a paucity of information concerning salivary molecules of Neotropical argasid ticks. Among this group of ticks, considering the number of human cases of parasitism, including severe syndromes and hospitalization, Ornithodoros brasiliensis can be considered one of the major Neotropical argasid species with impact in public health. Here, we describe the transcriptome analysis of O. brasiliensis salivary glands (ObSG). The transcriptome yielded ~14,957 putative contigs. A total of 368 contigs were attributed to secreted proteins (SP), which represent approximately 2.5% of transcripts but ~53% expression coverage transcripts per million. Lipocalins are the major protein family among the most expressed SP, accounting for ~16% of the secretory transcripts and 51% of secretory protein abundance. The most expressed transcript is an ortholog of TSGP4 (tick salivary gland protein 4), a lipocalin first identified in Ornithodoros kalahariensis that functions as a leukotriene C4 scavenger. A total of 55 lipocalin transcripts were identified in ObSG. Other transcripts potentially involved in tick-host interaction included as: basic/acid tail secretory proteins (second most abundant expressed group), serine protease inhibitors (including Kunitz inhibitors), 5' nucleotidases (tick apyrases), phospholipase A2, 7 disulfide bond domain, cystatins, and tick antimicrobial peptides. Another abundant group of proteins in ObSG is metalloproteases. Analysis of these major protein groups suggests that several duplication events after speciation were responsible for the abundance of redundant compounds in tick salivary glands. A full mitochondrial genome could be assembled from the transcriptome data and confirmed the close genetic identity of the tick strain sampled in the current study, to a tick strain previously implicated in tick toxicoses. This study provides novel information on the molecular composition of ObSG, a Brazilian endemic tick associated with several human cases of parasitism. These results could be helpful in the understanding of clinical findings observed in bitten patients, and also, could provide more information on the evolution of Neotropical argasids.